2019
DOI: 10.48550/arxiv.1909.07313
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Solving Strong-Substitutes Product-Mix Auctions

Abstract: This paper develops algorithms to solve strong-substitutes product-mix auctions. That is, it finds competitive equilibrium prices and quantities for agents who use this auction's bidding language to truthfully express their strong-substitutes preferences over an arbitrary number of goods, each of which is available in multiple discrete units. (Strong substitutes preferences are also known, in other literatures, as M -concave, matroidal and well-layered maps, and valuated matroids). Our use of the bidding langu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…The SSPMA is neither based on a value nor a demand oracle. 6 A collection of bids specifies a large number of package values, which mitigates the missing bids problem. This type of preference elicitation permits efficient ways to compute Walrasian prices, and allows us to uncover new properties of strong substitutes valuations.…”
Section: The Strong Substitutes Product-mix Auction (Sspma)mentioning
confidence: 99%
See 4 more Smart Citations
“…The SSPMA is neither based on a value nor a demand oracle. 6 A collection of bids specifies a large number of package values, which mitigates the missing bids problem. This type of preference elicitation permits efficient ways to compute Walrasian prices, and allows us to uncover new properties of strong substitutes valuations.…”
Section: The Strong Substitutes Product-mix Auction (Sspma)mentioning
confidence: 99%
“…More precisely, we show that the Toland-Singer dual [33,47] of L(p) is the minimum difference between the positive and negative linear programs. [6] have recently shown that a standard steepest-descent algorithm based on the Lyapunov function (following [38]) can solve the SSPMA pricing problem, but their method takes only limited advantage of the special features of the geometric representation. 14 By taking fuller advantage of the structure of strong substitutes analyzed in this paper, we find an alternative to steepest descent on the Lyapunov function.…”
Section: Our Contributionmentioning
confidence: 99%
See 3 more Smart Citations